2020
DOI: 10.1097/mcg.0000000000001454
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Right Colon Adenoma Miss Rates Between Water Exchange and Carbon Dioxide Insufflation

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 35 publications
(113 reference statements)
0
8
1
2
Order By: Relevance
“…6 WE decreased the miss rate of right colon adenomas 6,7 and serrated polyps. 7 WE produced significantly higher ADR than WI. 8 Network meta-analyses showed WE colonoscopy had the highest ADR, 9 advanced ADR 9 and serrated adenoma/polyp detection rate 10 compared with cap-and Endocuff-assisted colonoscopy when gas insufflation was used as the common comparator.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…6 WE decreased the miss rate of right colon adenomas 6,7 and serrated polyps. 7 WE produced significantly higher ADR than WI. 8 Network meta-analyses showed WE colonoscopy had the highest ADR, 9 advanced ADR 9 and serrated adenoma/polyp detection rate 10 compared with cap-and Endocuff-assisted colonoscopy when gas insufflation was used as the common comparator.…”
Section: Discussionmentioning
confidence: 92%
“…Compared with gas insufflation WE significantly increased overall advanced ADR, 5 right colon ADR 6 and serrated lesions detection rate 6 . WE decreased the miss rate of right colon adenomas 6,7 and serrated polyps 7 . WE produced significantly higher ADR than WI 8 .…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…On the other hand, CADe works as a second observer and points out polyps that are exposed but not recognized due to human error [ 17 ]. A single-center study clearly demonstrated that even WE missed polyps in the right colon [ 44 ]. In other words, the individual strengths of WE and CADe complement the weakness of one another.…”
Section: Water Exchange and Its Potential Beneficial Effect On Reducing Fpsmentioning
confidence: 99%